Genome-wide analysis of tobacco NtTOM1/TOM3 gene family and identification of NtTOM1a/ NtTOM3a response to tobacco mosaic virus - Wang, Xuebo; Bai, Yalin; Shen, Zhan; Zhang, Xinyao; Cai, Changchun; Qiao, Chan; Jiang, Caihong; Cheng, Lirui; Liu, Dan; Yang, Aiguo (BMC plant biology, 2024)
TOBAMOVIRUS MULTIPLICATION 1 (TOM1) and its homolog TOBAMOVIRUS MULTIPLICATION 3 (TOM3) play a prominent role in the multiplication of tobacco mosaic virus (TMV) in higher plants. Although homologs of NtTOM1/TOM3 genes have been identified in several plant species, little is known about the characteristics and functions of NtTOM1/TOM3 at the genome-wide level in tobacco (Nicotiana tabacum L.). In this study, we performed genome-wide identification and expression pattern analysis of the tobacco NtTOM1/TOM3 gene family. Twelve NtTOM1/TOM3 genes were identified and classified into four groups based on phylogenetic analysis. Sequence and conserved domain analyses showed that all these genes contained a specific DUF1084 domain. Expression pattern analysis showed that NtTOM1a, NtTOM1b, NtTOM1d, NtTOM3a, NtTOM3b, and NtTOM3d were induced by TMV at 1-, 3-, and 9 dpi, whereas the expression of other genes was not responsive to TMV at the early infection stage. TMV virion accumulation showed no obvious difference in either nttom1a or nttom3a mutants compared with the wild type. However, the virus propagation was significantly, but not completely, inhibited in the nttom1atom3a double mutant, indicating that other gene family members may function redundantly, such as NtTOM1b and NtTOM1d. In addition, overexpression of NtTOM1a or NtTOM3a also inhibited the TMV replication to some extent. The present study performed genome-wide analysis of the NtTOM1/TOM3 gene family in tobacco, and identified NtTOM1a and NtTOM3a as important genes involved in TMV multiplication based on functional analysis. These results provide a theoretical basis for further improving TMV resistance in tobacco.